Targeting tumor-associated macrophages for the immunotherapy of glioblastoma: Navigating the clinical and translational landscape - Wang, Zide; Zhong, Hanlin; Liang, Xiaohong; Ni, Shilei (Frontiers in Immunology, 2022)
Tumor-associated macrophages (TAMs) can directly clear tumor cells and enhance the phagocytic ability of immune cells. An abundance of TAMs at the site of the glioblastoma tumor indicates that TAM-targeting immunotherapy could represent a potential form of treatment for this aggressive cancer. Herein, we discuss: i) the dynamic role of TAMs in glioblastoma; ii) describe the formation of the immunosuppressive tumor microenvironment; iii) summarize the latest clinical trial data that reveal how TAM function can be regulated in favor tumor eradication; and lastly, iv) evaluate the implications of existing and novel translational approaches for treating glioblastoma in clinical practice.